Pharmacognostical, Phytochemical and Antioxidant Studies of Indigenous Medicinal Plant - Deokate, Uday; Upadhye, Mohini; Pujari, Rohini; Ambikar, Digambar (Current Bioactive Compounds, 2020)
Background: Ficus glomerata Roxb. is a moderate-sized avenue tree distributed throughout India both as wild or cultivated. It is traditionally used in various traditional systems of medicine including Ayurveda, Siddha and Homoeopathy. In these indigenous systems of medicine, different parts of the plant Ficus glomerata are commonly used for the treatment of dysentery, diarrhea, diabetes, bilious affections, stomachache, menorrhage, haemoptysis and also as a carminative and astringent. Objectives:The current investigation deals with detail pharmacognostical studies on roots of Ficus racemosa mainly focusing the morphological, macroscopical analysis, prelimilnary examinations of root powder and florescence analysis. Methods: Physicochemical constants of roots of Ficus glomerata were estimated as per official guidelines. Results: Significant in vitro antioxidant activity was observed for alcoholic root extract of Ficus glomerata. The alcoholic extract and aqueous extract show the presence of tannins and saponins as major constituents. Remaining constituents were found to be carbohydrate, glycosides, phenolic compounds, gum and mucilage. Conclusion: Ficus glomerata possess significant antioxidant activities.
Keywords: phytochemical investigation